Dinosaurs before dark - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1992)
Eight-year-old Jack and his younger sister Annie find a magic treehouse, which whisks them back to an ancient time zone where they see live dinosaurs.
"A First stepping stone book."
Keywords: Dinosaurs -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction